Cation deficiency effect on negative thermal expansion of ferroelectric PbTiO3. Issue 12 (19th October 2015) - Peng, Xin; Rong, Yangchun; Fan, Longlong; Lin, Kun; Zhu, He; Deng, Jinxia; Chen, Jun; Xing, Xianran
Abstract : This article describes a strong correlation between the spontaneous polarization and NTE features in 8% Pb 2+ deficient PT (P92 T), 2% Ti 4+ deficient PT (PT98 ) and pure PbTiO3 (PT) samples, which meets the mechanism of spontaneous volume ferroelectrostriction. Abstract : It is known that negative thermal expansion (NTE) in PbTiO3 (PT) ferroelectrics can be controlled by chemical substitutions. In the present work, however, we report a method to change the NTE of PT by introducing cation deficiency at both the A (Pb 2+ ) and B sites (Ti 4+ ). We investigated the spontaneous polarization, tetragonality c / a, coefficient of thermal expansion, and Curie temperature T C with 8% Pb 2+ deficient PT (P92 T), 2% Ti 4+ deficient PT (PT98 ), and pure PT. We found that while Pb 2+ deficiency distinctively weakens the NTE, the effect of B-site deficiency could be ignored. These phenomena are ascribed to the NTE mechanism of spontaneous volume ferroelectrostriction. The present study provides a possible way to control the NTE of PT-based materials.